Monetary Policy Shifts and the Term Structure - Ang, A.; Boivin, J.; Dong, S.; Loo-Kung, R. (Review of Economic Studies, 2011)
We estimate the effect of shifts in monetary policy using the term structure of interest rates. In our no-arbitrage model, the short rate follows a version of the Taylor's (1993, “Discretion Versus Policy Rules in Practice”, Carnegie-Rochester Conference Series on Public Policy, 39, 195–214) rule where the coefficients on the output gap and inflation vary over time. The monetary policy loading on the output gap has averaged around 0·4 and has not changed very much over time. The overall response of the yield curve to output gap components is relatively small. In contrast, the inflation loading has changed substantially over the last 50 years and ranges from close to zero in 2003 to a high of 2·4 in 1983. Long-term bonds are sensitive to inflation policy shifts with increases in inflation loadings leading to higher short rates and widening yield spreads.